Development of interactive multimedia based on blended learning to improve student science literacy during the covid-19 pandemic - Muhammad Shohibul Ihsan; Siti Wardatul Jannah (Department of Mathematics and Science Education, Faculty of Teacher Training and Education, University of Mataram. Jurnal Pijar MIPA colaborates with Perkumpulan Pendidik IPA Indonesia Wilayah Nusa Tenggara Barat, 2021)
This study aims at producing interactive multimedia that is valid, practical, and effective to improve students' scientific literacy in Chemistry subjects with the subject matter of oxidation-reduction reactions. This research is included in research and development refers to the ADDIE development model, including the Analysis, Design, Development, Implementation, and Evaluation stages. The interactive multimedia testing in learning and scientific literacy tests were conducted on students of Class X MIA MA Nahdlatul Wathan Suela, NTB. The design of this research trial used One Group Pretest-Posttest Design. The results showed that the average percentage of the interactive multimedia feasibility from three validators was 83.3%, with very feasible criteria. Scientific literacy instruments also got 82.6%, with very feasible criteria. The use of interactive multimedia in the limited trial got an average score of 80.6% from teachers and students with very practical criteria. Interactive multimedia effectively improves students' scientific literacy, marked by the difference in the average score of students' scientific literacy results from 32.05 to 85.41 with very effective criteria. These results show that the developed interactive multimedia has valid, practical, and effective criteria to improve students' scientific literacy during the covid-19 pandemic.